PERLINDUNGAN HUKUM BAGI KONSUMEN TERHADAP PENGGUNA KOSMETIK YANG TIDAK TERDAFTAR BADAN PENGAWASAN OBAT DAN MAKANAN (BPOM) (Studi Penelitian Di Kota Idi Kabupaten Aceh Timur) - ayu humaira; Yulia y; Fatahillah F (JURNAL ILMIAH MAHASISWA FAKULTAS HUKUM UNIVERSITAS MALIKUSSALEH, 2021)
Abstract/Digest Legal protection is very important for consumers. The government has provided legal protection for consumers as regulated in Article 4 of Law Number 8 of 1999 concerning Consumer Protection. Cosmetic consumers in Idi City use a lot of cosmetic products that are not registered with BPOM, as a result, skin damage occurs after the use is made by consumers. The people of Idi City as consumers of cosmetics are easily tempted by the effects of creams that can whiten the skin in a short period of time and the community does not have awareness of the legal protection rights they have. This study aims to identify and explain the legal protection for consumers who use cosmetics that are not registered with BPOM, to find out and explain the obstacles to BBPOM Banda Aceh in legal protection of consumers using cosmetics that are not registered at BPOM and BBPOM Banda Aceh efforts in resolving barriers to consumers. cosmetic users who are not registered with BPOM. This study uses a qualitative method with an empirical juridical approach. The data were obtained through library research and supported by field research. Data analysis was done descriptively (descriptive analysis). Based on the results of the study, it is known that the implementation of legal protection for consumers has not been implemented optimally. Barriers to consumer protection are the lack of knowledge of consumers and business actors about regulations related to cosmetics. The efforts made are prevention strategies (socialization with the community), surveillance strategies and enforcement strategies. It is suggested to the public to be wiser in choosing cosmetic products. Legal awareness for business actors in producing illegal cosmetics and carrying out their obligations as business actors in accordance with the laws and regulations and BPOM further enhances the cosmetic reducer in the market. Keywords: Legal Protection, Consumers, Cosmetics.